Embryo toxicity assay in the fish species Rhamdia quelen (Teleostei, Heptaridae) to assess water quality in the Upper Iguacu basin (Parana, Brazil) - Brito, Izabella de Andrade; Esquivel Garcia, Juan Ramon; Salaroli, Alexandre Barbosa; Lopes Figueira, Rubens Cesar; Martins, Cesar de Castro; Cordeiro Neto, Alexandre; Gusso-Choueri, Paloma Kachel [UNESP]; Choueri, Rodrigo Brasil; Lino Araujo, Sabrina Borges; Oliveira Ribeiro, Ciro Alberto de (Elsevier B.V., 2018)
The Iguacu River is one of the largest and most important rivers in the Southern of Brazil. The Upper Iguacu Basin is responsible for water supply (80%) of the Metropolitan Region of Curitiba (MRC). After crossing a large urban region, the river is polluted by domestic and industrial sewage, but despite of that few ecotoxicological studies have been performed in order to evaluate the water quality from Iguacu River. The aim of the present study was to investigate the risk of exposure of Iguacu water to biota and also human population. In this terms, was utilized the survival effect and the morphological deformities in larval embryos of Rhamdia quelen, a native South America species. The results showed a high level of pollution in all studied sites along the Upper Iguacu River including PAHs and toxic metals such as lead. The lethal and non-lethal effects described in earlier stages of development suggest an elevated risk to biota. This data was corroborated by the theoretical model, showing that the pollutants present in water from Iguacu River may further reduce the fish population density including risk of local extinction. The present study reflect the needs to conduct in-depth research to evaluate the real impact of human activities on the endemic fish biota of Iguacu River including the risk for human populations. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Iguacu river; Embryo toxicity; Ecological modeling; Rhamdia quelen; Water quality